1991
DOI: 10.1200/jco.1991.9.12.2110
|View full text |Cite
|
Sign up to set email alerts
|

Extended continuous infusion low-dose recombinant interleukin-2 in advanced cancer: prolonged immunomodulation without significant toxicity.

Abstract: In previous clinical trials, recombinant interleukin-2 (rIL-2) has been infused at high doses over short periods of time to generate lymphokine-activated killer (LAK) cells in vivo. These trials have been limited by severe toxicities, and the immunologic effects of rIL-2 have been transient. The present study was designed to assess the toxicity and immunologic effects of prolonged administration of low doses of rIL-2. In this phase I study, patients with advanced cancer were scheduled to receive intravenous (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 20 publications
3
34
1
Order By: Relevance
“…9,[117][118][119][120] In most studies, it has been difficult to convincingly demonstrate a clinical benefit, especially in small phase I and II clinical trials. Although it is not known to what extent cytokines, such as IL-2, may alter the balance between activating and inhibitory receptors on NK cells, it is likely that the inhibitory signals delivered by MHC class I molecules expressed on the autologous target cancer are a major limitation to successful treatment.…”
Section: Clinical Roles Of Nk Cell Receptors: Stem Cell Transplantatimentioning
confidence: 99%
“…9,[117][118][119][120] In most studies, it has been difficult to convincingly demonstrate a clinical benefit, especially in small phase I and II clinical trials. Although it is not known to what extent cytokines, such as IL-2, may alter the balance between activating and inhibitory receptors on NK cells, it is likely that the inhibitory signals delivered by MHC class I molecules expressed on the autologous target cancer are a major limitation to successful treatment.…”
Section: Clinical Roles Of Nk Cell Receptors: Stem Cell Transplantatimentioning
confidence: 99%
“…Low concentrations of IL-2 are known to induce the cytotoxic effector function of NK cells in vitro [12]. Low dose continuous rIL-2 has been safely applied to patients with solid tumors [34] and to those who had undergone autologous or allogeneic transplant [45]. In both settings, companion studies demonstrated that NK cells obtained from patients receiving IL-2 were active and could kill surrogate targets.…”
Section: Discussionmentioning
confidence: 99%
“…We previously conducted several studies assessing prolonged continuous infusion of low dose rIL-2 for patients with metastatic solid cancers [34,35]. Treatment was very well tolerated and immunophenotypic analysis of peripheral blood mononuclear cells revealed a significant increase in NK cells with a less notable change in T-cell number.…”
Section: Introductionmentioning
confidence: 99%
“…The immunological changes may be summarised by the expression of activation markers, as well as by the amplification of the NK and LAK functions and by the in vivo release of two cytokines-IFN gamma and Tumour Necrosis Factor (TNFa)-with known anti-proliferative activity Hank et al, 1988;Gottlieb et al, 1989;Heslop et al, 1989;Foa et al, 1991b). (West et al, 1987), continuous infusion protocols using a daily dose escalating scheme (Foa et al, 1990b;1991a), prolonged low-dose daily infusion (Caligiuri et al, 1991), as well as loco-regional injections of IL2 directly in the tumour area or around tumour-draining lymphnodes (Cortesina et al, 1988 More relevantly, the constitutive release of IL4 (Tepper et al, 1989;Golumbek et al, 1991), IL6 (Porgador et al, 1992), IL7 (Hock et al, 1991), IFN gamma (Watanabe et al, 1989;Gansbacher et al, 1990a), TNF alpha (Blankenstein et al, 1991;Asher et al, 1991) and G-CSF (Colombo et al, 1991) by the genetically engineered tumour cells has resulted in a decreased or abrogated tumorigenicity. The mechanisms by which this anti-tumour response, induced by the release of the different cytokines and growth factors, is obtained is most likely heterogeneous, including in some models local intra-tumoural inflammation and in others the generation of cytotoxic T-lymphocytes.…”
Section: Il2 In the Management Of Cancer Patientsmentioning
confidence: 99%